A review of solid-state proton polymer batteries: materials and characterizations - Rani, M. S. A.; Norrrahim, M. N. F.; Knight, V. F.; Nurazzi, N. M.; Abdan, K.; Lee, S. H. (Multidisciplinary Digital Publishing Institute, 2023)
The ever-increasing global population necessitates a secure and ample energy supply, the majority of which is derived from fossil fuels. However, due to the immense energy demand, the exponential depletion of these non-renewable energy sources is both unavoidable and inevitable in the approaching century. Therefore, exploring the use of polymer electrolytes as alternatives in proton-conducting batteries opens an intriguing research field, as demonstrated by the growing number of publications on the subject. Significant progress has been made in the production of new and more complex polymer-electrolyte materials. Specific characterizations are necessary to optimize these novel materials. This paper provides a detailed overview of these characterizations, as well as recent advancements in characterization methods for proton-conducting polymer electrolytes in solid-state batteries. Each characterization is evaluated based on its objectives, experimental design, a summary of significant results, and a few noteworthy case studies. Finally, we discuss future characterizations and advances.